Export Behavior and Board Independence in Colombian Family Firms: The Reverse Causality Relationship (2016)
In the context of greater market liberalization in Latin America, one issue that merits greater attention for empirical investigation is the international expansion of family-owned business. Specifically, the relationship between export behavior, family control and board composition in the Latin American context is absent in the literature. Using a large and unique database from Colombian firms (33,249 firms in the period of 2008 to 2013), we provide insightful information on the determinants of export behavior of family firms in emerging markets. Our empirical test confirms an endogenous relation between boards’ composition (specifically the presence of independent members) and export behavior in family firms. Firms with a higher participation of independent board members are more likely to exhibit higher levels of exports. A "virtuous cycle" was also detected whereby the introduction of independent members on the board can be expected to boost export behavior, which in turn will encourage the increase of independent members on the board of private firms.